The roles of embodiment, emotion and lifeworld for rationality and agency in nursing practice - Benner, Patricia (Nursing philosophy, 2000)
Nursing practice invites nurses to embody caring practices that meet, comfort and empower vulnerable others. Such a practice requires a commitment to meeting and helping the other in ways that liberate and strengthen and avoid imposing the will of the caregiver on the patient. Being good and acting well (phronesis) occur in particular situations. A socially constituted and embodied view of agency, as developed by Merleau-Ponty, provides an alternative to Cartesian and Kantian views of agency. A socially constituted, embodied view of agency is less mechanistic and less deterministic than Descartes' and Kant's radical separation of mind and body, and more responsive and generative than Kant's vision of moral agency as constituted by autonomous choice makers who are uninfluenced by emotion. The role of emotion in perception and judgement is explored in this paper. Distinctions between techne and phronesis are drawn. The role of emotion in market relationships and procedural ethics drawn for the abstract, general other are strategies for exchange of goods and services, but these same market relationships are dependent on well-functioning nonmarket relations of noncalculated giving and receiving.